Wall Climbing Robot: Mechanical Design and Implementation - Albagul, Abdulgani; Asseni, A.; Khalifa, Othman Omran (2011)
A wall climbing robot is a robot with the capability of climbing vertical surfaces. This paper describes the design and fabrication of a quadruped climbing robot. We are required to design and create a wall climbing robot which uses suction as a means of sticking to the wall. The robot will be controlled using Basic Stamp and the movement of its legs will generated by two servo motors. Each servo motor will control legs which are located on the left and right side of the robot. The leg rotations mimic stepping motions through the use of a slider and crank. The suction force will be supplied by two vacuum pumps that will turn on intermittently. The main body of the robot will carry all the components except for the compressor thus making it mobile. Currently the robot is only designed for linear movement. However plans to incorporate maneuverability and other functions can be implemented after the first stage of the development achievessuccess.